2021
DOI: 10.1093/gji/ggab408
|View full text |Cite
|
Sign up to set email alerts
|

Profiling the Quito basin (Ecuador) using seismic ambient noise

Abstract: Summary Quito, the capital of Ecuador, with more than 2.5 M inhabitants, is exposed to a high seismic hazard due to its proximity to the Pacific subduction zone and active crustal faults, both capable of generating significant earthquakes. Furthermore, the city is located in an intermontane piggy-back basin prone to seismic wave amplification. To understand the basin’s seismic response and characterize its geological structure, 20 broad and medium frequency band seismic stations were deployed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…(2022) and Pacheco et al. (2022) showed that, for different stacking periods, the SNR values of NCFs from the ts‐PWS are higher than that from the linear stack. To show the surface wave clearly, in Figure 3a, we only plot 500 NCFs that vary with the interstation distance in the 0.3–8s period band.…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…(2022) and Pacheco et al. (2022) showed that, for different stacking periods, the SNR values of NCFs from the ts‐PWS are higher than that from the linear stack. To show the surface wave clearly, in Figure 3a, we only plot 500 NCFs that vary with the interstation distance in the 0.3–8s period band.…”
Section: Methodsmentioning
confidence: 95%
“…The ts-PWS can greatly improve the signal-to-noise ratio (SNR) and Empirical Green's functions (EGFs) convergence compared with the linear stack (Ventosa et al, 2017). The results of Shekar et al (2022) and Pacheco et al (2022) showed that, for different stacking periods, the SNR values of NCFs from the ts-PWS are higher than that from the linear stack. To show the surface wave clearly, in Figure 3a, we only plot 500 NCFs that vary with the interstation distance in the 0.3-8s period band.…”
Section: Ambient Noise Cross-correlation Functionsmentioning
confidence: 99%
“…Major earthquake disasters such as Mexico City (1985), Kobe (1995) and more recently Turkey-Syria (2023) have demonstrated the increase in hazard caused by the ampli cation of seismic waves in soft soils (e.g., Kramer, 1996). However, this topic remains in its infancy in the Andes, limited almost exclusively to the capital cities (Santiago: Pilz et al, 2009; Lima: Calderon et al, 2014; Quito: Pacheco et al, 2022). As a fast-growing touristic town with uncontrolled planning, the city of Cusco turns out to be a crucial case study.…”
Section: Introductionmentioning
confidence: 99%